A comparative analysis of extraction protocol performance on degraded mammalian museum specimens - Hawkins, Melissa T. R.; Flores, Mary Faith C.; McGowen, Michael; Hinckley, Arlo (Frontiers in Ecology and Evolution, 2022)
The extraction of nucleic acids is one of the most routine procedures used in molecular biology laboratories, yet kit performance may influence the downstream processing of samples, particularly for samples which are degraded, and in low concentrations. Here we tested several commercial kits for specific use on commonly sampled mammalian museum specimens to evaluate the yield, size distribution, and endogenous content. Samples were weighed and had approximately equal input material for each extraction. These sample types are typical of natural history repositories ranged from 53-130 years old. The tested protocols spanned spin-column based extractions, magnetic bead purification, phenol/chloroform isolation, and specific modifications for ancient DNA. Diverse types of mammalian specimens were tested including adherent osteological material, bone and teeth, skin, and baleen. The concentration of DNA was quantified via fluorometry, and the size distributions of extracts visualized on an Agilent TapeStation. Overall, when DNA isolation was successful, all methods had quantifiable concentrations, albeit with variation across extracts. The length distributions varied based on the extraction protocol used. Shotgun sequencing was performed to evaluate if the extraction methods influenced the amount of endogenous versus exogenous content. The DNA content was similar across extraction methods indicating no obvious biases for DNA derived from different sources. Qiagen kits and phenol/chloroform isolation outperformed the Zymo magnetic bead isolations in these types of samples. Statistical analyses revealed that extraction method only explained 5% of the observed variation, and that specimen age explained variation (29%) more effectively.